Knowledge, Attitude and Practices Survey: COVID-19 Pandemic and its Preventive Standard Operating Procedures in College Students - Rabiya Ali; Muhammad Jawad; Alishba Jawed; Muhammad Afzal; Azka r Maryam Zafar (Aziz Fatimah Medical and Dental College, 2021)
Objectives: To evaluate the knowledge, attitude and practices of the undergraduate college students towards corona virus disease (COVID-19) and adoption of personal protective measures as per standard operating procedures (SOPs) stipulated by Federal government for reopening of educational institute. Methodology: This was cross sectional survey conducted at Hyderabad and Faisalabad based colleges form 25 September to 15 October 2020. Prior to the study, permission was taken from principal of concerned colleges (vide no.TSS/22/2021, Kotri Jamshoro) Structured proforma comprised of 28 questions concerning knowledge, attitude and practices toward the COVID-19 and implementation of SOPs in educational institutes was used. Questionnaire was formed on Google form and its link was shared among 200 college students of various disciplines through WhatsApp. Results from the response summary were compiled and analyzed. Results: Structured proforma was distributed among 200 undergraduate students of age range18-20 years, only 170 students' submitted complete responses. Response rate was 85%. More than half (70.9%) of the subjects have good knowledge and positive attitude concerning COVID-19. Majority of the students (89.2%) were using masks, 88.6% were in habit of regular hand washing ,while 84.3 % of students preferred to use sanitizers, 91.6% practiced social distancing and avoided crowded places ,75.3% students avoided unnecessary travelling. 98-99% of students agreed that SOPs set by government was strictly followed in the colleges. Conclusion: Majority of the students were aware of the preventive measures for COVID outbreak. Students have positive attitude and are adequately practicing precautionary measures to avoid contracting COVID-19. SOPs are following in the colleges to alleviate the risk of spread of lethal Corona.